Relationship Between Polypharmacy and Frailty in Older Adults: Which Frailty Assessment Tool Shows the Relationship Best? - CAKMAK, Guzin; Öztürk, Zeynel Abidin (Progress in Nutrition, 2021)
Frailty syndrome is one of the geriatric syndromes that carries an increased risk for adverse health outcomes. This study aims to investigate the relationship between frailty and polypharmacy in the elderly. This cross-sectional study was conducted for a period of 4 months from September 2019 to January 2020. Frailty was assessed by using the Fried Frailty Index (FFI) and SOF (Study of Osteoporotic Fractures) Index. Patients were evaluated for inappropriate medication use by TIME (Turkish Inappropriate Medication Use in the Elderly) criteria. Data analysis was done by using SPSS version 22. The study population was composed of 93 women and 57 men, and the mean age was 73 +/- 9 years. The frequency of polypharmacy was %73 (n=110). Presence of polypharmacy and number of drugs used were related to both FFI and SOF index scores. We found that the FFI score was associated with number of drugs used in regression analysis (r²=0.166, p<0.001). The relationship between multimorbidity and frailty was also demonstrated by FFI(p=0.01). We showed a cut-off value of 6.5 of drug numbers for being frail according to the FFI index in the ROC curve (sensitivity:68%; specificity:62%; p<0.001; CI:95%; AUC:0.693). The frequency of inappropriate medicine use was 38%. In this study, we revealed that frailty was related to polypharmacy. We also found that FFI reveals the relationship between polypharmacy and frailty more precisely than the SOF index. Prospective studies to evaluate the effect of decreasing the number of used drugs on frailty could be useful.